Higher Education Expansion and Supply of Teachers in China - Fengyan Dai; Lei Xu; Yu Zhu (Institute of Labor Economics (IZA), 2021)
We examine the teacher labour market in China using the 2005 mini-Census, in the context of the transformation of the world's largest education system. We first document a significant increase not only in quantity, but also in quality of teachers during 1990-2005. Instrumental Variables results based on the natural experiment of a substantial expansion of higher education in 1992/93 indicate a large positive causal effect of the expansion on supply of teachers. Consistent with differential opportunity costs across graduate occupations, the supply effect is more pronounced for women and those living in less developed regions. Further analyses of differential college premiums in earnings and non-pecuniary benefits between teaching and non-teaching occupations suggest that teacher recruitment has become more market-oriented and flexible, in attracting low to lower-middle ability college graduates into teaching in an increasingly decentralized and competitive graduate labour market.
Keywords: I23; I26; J45; 330; college premium; higher education expansion; supply of teachers; China; instrumental variables; non-pecuniary benefits